Prevention of Sexual Child Abuse: Preliminary Results From an Outpatient Therapy Program - Wild, Tamara S. N.; Müller, Isabel; Fromberger, Peter; Jordan, Kirsten; Klein, Lenka; Müller, Jürgen L. (Frontiers in Psychiatry, 2020)
In Germany, access to outpatient treatment services devoted to the prevention of (further) sexual offences against minors and child sexual exploitation material offences often is limited. The therapy project “Prevention of Sexual Abuse” tries to fill this gap by providing treatment to patients with a self-reported sexual interest in children and adolescents, irrespective of whether or not they are pedophilic or prosecuted by the legal justice system. Within the project, a treatment manual was developed which specifically addresses dynamic risk-factors in child sexual abusers and child sexual exploitation material offenders. The treatment manual was conceived to reduce recidivism risk and to contribute to the enhancement of the patients’ personal well-being. In this paper, results of the accompanying scientific research are presented: Offense-supportive attitudes (N = 23), self-reported child sexual exploitation material use (N = 10), emotional distress (N = 24), and participants’ subjective risk perception of committing (further) sexual offenses (N = 25) reduced during the course of treatment. A reduction of offense-supportive attitudes was further observed from pre-intervention to one-year follow-up (N = 8). Changes with regard to self-efficacy, quality of life, participants’ self-perceived ability to control sexual impulses towards children and adolescents permanently, and several measures assessing different kinds of sexual recidivism did not, however, reach any level of significance. During an average observation period of 2.4 years, six patients confessed to have conducted new sexual exploitation material offenses, while no further sexual abuse cases were reported (N = 19). Due to the used research design and small sample sizes, treatment effects cannot be inferred and external validity is limited. This notwithstanding, results provide first evidence for a relationship between treatment participation and self-reported recidivism and psychological well-being.